Executive Share Ownership on Risk Taking Among the Listed Commercial Banks in Kenya - Njogu, Lucy Wanjiru; Gekara, Dr. Mouni; Waititu, Dr. Gichuhi A.; Omido, Dr. Karim (European Journal of Business and Strategic Management, 2017)
Abstract Purpose: The purpose of this study was to determine the effect of Executive Share Ownership on Risk Taking among the Listed Commercial Banks in Kenya. Methodology:The study used an Epistemology research philosophy, causal research design was adopted whereby panel data approach was used. The target population for this study were the 11 listed banks on the NSE. Secondary Data for the year 2010 to 2015 was collected from the NSE handbook. Data collected was analyzed using descriptive statistics which included means and standard deviations. Inferential statistics such as Pearson correlation and panel regression was also used. The results were presented in form of tables, figures, charts, graphs and trend lines. Results:Based on the findings, the study concluded that there Share Ownership and risk taking are positively and insignificantly related. Policy recommendation: This study recommends that on Executive Share Ownership banks should not increase director's shares as this will have no effect on risk taking.